Weight in infancy and adult calcium absorption as determinants of bone mineral density in adult men: the Hertfordshire cohort study. - Patel, M; Makepeace, A; Jameson, K; Masterson, L; Holt, R; Swaminathan, R; Javaid, M; Cooper, C; Arden, N (2012)
Adult bone mass is modified by early life environmental influences, but the mechanism of this association is uncertain. Data support an inverse relationship between intestinal calcium absorption (αCa) and birth weight in women. However, little is known regarding determinants in men. This study examines the association between weight in infancy and adult αCa in healthy men and whether this could be a mechanism by which the early life environment may influence bone mass. Men were recruited from the MRC Hertfordshire Cohort Study, for whom detailed early life records were available. Areal bone mineral density (aBMD) was measured using a Hologic QDR 4500 at the femoral neck (FN) and lumbar spine. We randomly selected 123 men stratified by birth weight and assessed αCa using the stable strontium absorption test. The mean age was 63.6 (SD 2.5) years. αCa was not associated with birth weight or weight at 1 year. FN aBMD was associated with both weight at 1 year (r = 0.20, p = 0.03) and αCa (r = 0.20, p = 0.03). Both of these associations remained statistically significant in a mutually adjusted, multivariable model but would account for only ~4 % variance in BMD. We demonstrated a positive association between weight at 1 year and aBMD and between αCa and FN BMD, but no association was found between birth weight and αCa. This suggests that in men, although αCa is a contributing factor in FN bone density, it is not the main mechanism whereby the early environment modifies adult BMD.